Exploring the Needs of Spousal, Adult Child, and Adult Sibling Informal Caregivers: A Mixed-Method Systematic Review - Dang, Srishti; Looijmans, Anne; Ferraris, Giulia; Lamura, Giovanni; Hagedoorn, Mariët (Frontiers in Psychology, 2022)
Informal caregivers (ICGs) provide care to their family or friends in case of an illness, disability, or frailty. The caregiving situation of informal caregivers may vary based on the relationship they have with the care recipient (CR), e.g. being a spouse or being an adult child. It could be the case that these different ICGs also have different needs. This study aims to explore and compare the needs of different groups of ICGs based on the relationship they have with their CR. We conducted a systematic review, performing a search in the databases PubMed, CINAHL, and PsycINFO. We included studies describing the needs of different groups of ICGs (e.g. spousal ICGs) and having qualitative, quantitative, or mixed-method study designs. We analyzed the data using the thematic analysis method. We included 22 articles (18 qualitative; 4 quantitative). The included articles reported the needs of ICGs taking care of a spouse (spousal ICGs), parent (adult child ICG), or sibling aged 18 years or above (adult sibling ICGs). We did not include other relationships due to the limited number of articles on these relationships. The most prominent needs reported by the spousal, adult child, and adult sibling ICGs were the need for information and need for support. The three groups differed in their needs as well. Adult child and adult sibling ICGs indicated a need to be acknowledged by the people around them for their role of carer, while they also needed to be seen as an individual having their own personal needs. Moreover, Spousal ICGs indicated a unique need of redefining their role and relationship with their CR. Overall, findings indicate that along with experiencing common needs, the investigated groups have unique needs as well. Thus, knowing the needs of different groups of ICGs can help develop tailored solutions to improve the quality of life of the ICGs and their CR.